Erysiphe macleayae R. Y. Zheng et G. Q. Chen (order Erysiphales) – a new invasive species in Belarus - Hirilovich, Ivan S.; Lemeza, Nikolai A. (Experimental Biology and Biotechnology, 2017)
A new invasive species of Erysiphe parasitizing Chelidonium majus recorded in Belarus. The morphometric characteristic and location of Erysiphe macleayae R.Y. Zheng et G. Q. Chen (order Erysiphales) are given.
Keywords: invasion; powdery; mildews; anamorphic; teleomorphic; Oidium; Pseudoidium; Macleaya; Chelidonium; Papaveraceae